Study of student - academic perception of implementation virtual teaching UCTemuco - Simian Fernandez, Mª Paula; Alvarez Saavedra, Eugenia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The 2020-21 confinement forced humanity to adapt to the new way of life and create new scenarios with technologies that transformed physical and traditional teaching spaces, abruptly replaced by virtual scenarios. This cross-sectional, exploratory and descriptive study, carried out by applying forms and semi-structured interviews to students and teachers of Design UCTemuco; collected the perception and implementation of distance teaching carried out and evaluated the face-to-face return. We raise strengths, difficulties and opportunities in this new form of teaching that challenges us by questioning ourselves as a result of acquired learning, emerging methodologies, educational platforms and institutional internationalization policies.